Evaluating Empirical Models of Lake Methane Emission and Surface Water Concentration across Hemiboreal to Subarctic Regions - Schenk, Jonathan (Linköping University, 2022)
Data on Lake Methane Emission and Surface Water Concentration across Hemiboreal to Subarctic Regions.

The dataset was originally published in DiVA and moved to SND in 2024.

Data om metanutsläpp från sjöar och ytvattenkoncentration i hemiboreala till subarktiska regioner.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Evaluating Empirical Models of Lake Methane Emission and Surface Water Concentration across Hemiboreal to Subarctic Regions
Keywords: lakes; sjöar; greenhouse gases; växthusgaser; surface water; ytvatten; methane; metan; Environmental Sciences; Miljövetenskap